2016
DOI: 10.3177/jnsv.62.330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Proton Pump Inhibitor Therapy on Nutritional Status in Elderly Hospitalized Patients

Abstract: SummaryThe purpose was to investigate the association between proton pump inhibitor (PPI) therapy and nutritional status in elderly hospitalized patients. Participants were 190 elderly patients admitted to the long-term care wards, convalescence rehabilitation wards, and community integrated care wards in January 2015. Nutritional status was assessed using the mini nutritional assessment short-form (MNA-SF). The PPI use group was compared with the PPI non-use group regarding nutrition status. Logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several studies have examined the association between long-term PPI use and the risk of developing vitamin B 12 deficiency [35,36]; most, [36] but not all [37], studies reported a 2-to 4-fold increased risk of vitamin B 12 deficiency associated with PPI therapy. The complex relationship between PPI use and nutritional status has not been fully elucidated.…”
Section: Proton Pump Inhibitors (Ppis)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the association between long-term PPI use and the risk of developing vitamin B 12 deficiency [35,36]; most, [36] but not all [37], studies reported a 2-to 4-fold increased risk of vitamin B 12 deficiency associated with PPI therapy. The complex relationship between PPI use and nutritional status has not been fully elucidated.…”
Section: Proton Pump Inhibitors (Ppis)mentioning
confidence: 99%
“…The complex relationship between PPI use and nutritional status has not been fully elucidated. However, it has been reported that the long-term use of PPIs may improve nutritional status in elderly patients admitted to a long-term care ward, convalescent rehabilitation ward, or community-integrated care ward [35].…”
Section: Proton Pump Inhibitors (Ppis)mentioning
confidence: 99%